Three new sea stars (Asteroidea: Solasteridae & Pterasteridae) from the Aleutian Islands - Clark, Roger N.; Jewett, Stephen C. (Zootaxa, 2011)
Two new species of Solaster, and a new species of Pteraster are described from the nearshore waters of the Aleutian Islands and compared to congeners from the region. Solaster hexactis sp. nov., S. spectabilis sp. nov., and Pteraster willsi sp. nov., are distinguished by the characteristics of the paxillar, marginal and adambulacral spines, and (in Solaster), the number of rays. The distributions of the new species and keys are provided.